UTILIZATION OF MISCROSOFT POWERPOINT MEDIA IN ISLAMIC AGE EDUCATION LEARNING AT MTS NEGERI 1 SURAKARTA - Kholadan, Ahmad Alamul Huda; Inayati, Nurul Latifatul (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This research discusses the utilization of Microsoft PowerPoint media in learning Islamic Religious Education (PAI) at MTs Negeri 1 Surakarta in the era of Industrial Revolution 4.0 and society 5.0. Rapidly developing information technology demands innovation in learning methods, including the use of digital media such as PowerPoint. The results showed that the use of PowerPoint facilitates the delivery of the material, increases student enthusiasm, and supports learning effectiveness. However, obstacles include high license fees and training needs for teachers. In conclusion, PowerPoint is an effective learning medium in supporting Islamic education objectives, subject to the challenges.